2018
DOI: 10.1080/14498596.2018.1472046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of advanced troposphere models for aiding reduction of PPP convergence time in Australia

Abstract: This paper firstly analyses the precision of tropospheric zenith total delay (ZTD) values obtained from the empirical models GPT2 and GPT2w, and the numerical weather models (NWM) from Australian Bureau of Meteorology (BoM), and European Centre for Medium-Range Weather Forecasts (ECMWF). Comparison of these ZTD values with IGS ZTD product at four sites showed that the ZTDs from NWM datasets were more precise than the empirical models. The ZTD from BoM data gave the best results, with mean errors between-0.034m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Probabilities of correct detection P CD and statistical overlap P ol for the two soft constraints A and D (Cluster 5) with σ c = 10mm and for α = 0.001.Similar effects of the relaxation of the constraints on the performance of the IDS in case of two soft constraints are verified in case of three soft constraints, as can be seen in theFigures 9,10, 11 and 12. …”
supporting
confidence: 62%
See 1 more Smart Citation
“…Probabilities of correct detection P CD and statistical overlap P ol for the two soft constraints A and D (Cluster 5) with σ c = 10mm and for α = 0.001.Similar effects of the relaxation of the constraints on the performance of the IDS in case of two soft constraints are verified in case of three soft constraints, as can be seen in theFigures 9,10, 11 and 12. …”
supporting
confidence: 62%
“…Such constraints are a prior knowledge embedded into a model to avoid a trivial solution; to guarantee the stability of estimates; to improve the precision and accuracy of the results by reducing the number of unknown parameters or accordingly by increasing the redundancy of the system; and to mitigate (or even estimate) a possible systematic effect [1][2][3]. For example, [4] adopted constraints to determine the transponder coordinates in a problem of combining satellite positioning (GNSS) of a surface platform with acoustic ranging to seafloor transponders; [5][6][7][8][9][10] have used constraints to model the atmospheric effects on GNSS signals; and [11] have imposed the constraints of predicted satellite clocks to improve the precise orbit determination (POD) processing during maneuvers.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical weather models (NWMs) are important data sources for space geodetic techniques; NWM-derived tropospheric delays are widely used in various geodetic techniques, such as Very Long Baseline Interferometry (VLBI) (Landskron and Böhm 2018a), Satellite Laser Ranging (SLR) (Mendes et al 2002), Satellite Altimetry (SA) (Vieira et al 2022), Interferometric Synthetic Aperture Radar (InSAR) (Foster et al 2006), and Global Navigation Satellite System (GNSS) (Lu et al 2017;Wilgan et al 2017). Numerous scholars have found and validated that NWM enhances the wet tropospheric correction retrieval of SA (Vieira et al 2022), improves the troposphere delays in SLR (Boisits et al 2020), provides more accurate gradient information to VLBI (Hofmeister and Böhm 2017), reduces GNSS positioning convergence time, and exhibits better overall robustness (Lu et al 2016(Lu et al , 2017Vaclavovic et al 2017;Deo and El-Mowafy 2018). Multiple tropospheric delay models (Schüler 2014;Li et al 2014Li et al , 2015Yang et al 2021), temperature and pressure models (Boehm et al , 2015Lagler et al 2013;Landskron and Böhm 2018b), weighted mean temperature models (Zhu et al 2022), mapping function models (Urquhart et al 2014;Zus et al 2015), and tropospheric gradient models have been developed based on different NWMs; they are typically used for correction or as a priori inputs in the above techniques (Wang et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The tropospheric delay can also be obtained from the global or regional numerical weather model (NWM). Research showed that the accuracy of the tropospheric delay obtained from NWM is better than that predicted by empirical models [32][33][34]. Usually, the ZHD is fixed with a model-predicted value and the ZWD is estimated as an unknown parameter in the PPP data-processing.…”
Section: Introductionmentioning
confidence: 99%